Análisis de la incidencia de la producción y exportación del sector panelero en el empleo del departamento del Tolima entre 2017 a 2023 - Sánchez Pérez, Luis Alejandro (Universidad Antonio Nariño, 2024)
A study was conducted to analyze how production and exportation in the panela sector impact employment generation in the Tolima department. The research aimed to answer the question: "What is the impact of panela sector production and exportation on employment in the Tolima department, considering the period from 2017 to 2020?" This study utilized a quantitative approach and relied on data from public statistical sources to support its findings.